Risk management and risk communication in Mozambique: the case of arms and ammunition depots of Malhazine - Bussotti, L. (Problems of Management in the 21st Century, 2017)
Risk management and risk communication affect everybody’s daily life. Local authorities have the duty to manage public structures, to inform civilians of the risks coming from these structures, to implement prophylaxis procedures. Military storage sites are fully included in this category. This article presents – through a qualitative methodology based on risk analysis – how risk management and communication in weapons and ammunition warehouses is managed in a “partially free” country, using as a case-study, the Malhazine depot in Mozambique, which resulted in more than 100 deaths. In 2007, an extraordinary accident related to the management of obsolete conventional weapons occurred at the Malazhine warehouse. In this circumstance, the Mozambican Government adopted a policy of classifying the information “highly confidential”. This policy aimed at obscuring facts and responsibilities by hiding the causes of such a huge tragedy. This article concludes with the consideration that a high level of confidentiality in treating issues of public interest, such as the one kept in regard to Malhazine, does not help public authorities to effectively manage and prevent similar risks from occurring again, with resulting negative impacts on local populations.